Being active for a purpose: Evaluating the bi-directional associations between monthly purpose and physical activity. (October 2022) - Pfund, Gabrielle N.; DeLongis, Anita; Sin, Nancy; Morstead, Talia; Hill, Patrick L.
Abstract: Background: Sense of purpose is a salient predictor of health outcomes, at least partially because individuals with a higher sense of purpose appear to engage in healthier lifestyle behaviors. Yet, little work has considered the role that greater physical activity may play in allowing individuals to maintain or develop a higher sense of purpose. Methods: Using five waves of monthly data (total n  = 2337), the current study investigates the bi-directional association between sense of purpose and monthly reports of average time spent per day in moderate and vigorous physical activity utilizing Random Intercept Cross-Lagged Panel models. Results: Findings suggested differences based on physical activity intensity. For moderate physical activity, concurrent within-person associations revealed that during months when sense of purpose was higher relative to a person's usual level, they also spent more time than usual engaging in moderate physical activity. Bi-directional cross-lagged effects indicated that higher sense of purpose predicted more next-month moderate physical activity, and vice versa. Only between-person associations were evident for vigorous physical activity, such that people with a higher sense of purpose on average spent more time in vigorous physical activity on average. The discussion focuses on the methodological advances of the current study, as well as implications for future research. Highlights: Purpose and moderate physical activity (e.g., walking) are associated within-person. Purpose and vigorous physical activity (e.g., running) are associated between-person. The associations between sense of purpose and physical activity do not differ based on age.